2017
DOI: 10.1051/epjconf/201716201052
|View full text |Cite
|
Sign up to set email alerts
|

Physical and electrical properties of SrTiO3and SrZrO3

Abstract: Abstract. Perovskite type oxide strontium titanate (SrTiO3) and strontium zirconate (SrZrO3) ceramic powder has been synthesized using conventional solid state reaction method. The powders were mixed and ground undergone calcinations at 1400 o C for 12 h and sintered at 1550 o C for 5h. X-ray Diffraction exposes physical properties SrTiO3 which exhibit cubic phase (space group: pm-3m) at room temperature meanwhile SrZrO3 has Orthorhombic phase (space group: pnma). The electrical properties such as dielectric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 18 publications
3
14
0
Order By: Relevance
“…In addition, we also investigated the temperature dependence of the relative permittivity in the temperature range from 20 to 80 • C at 1 MHz. The results showed that a typical value of the temperature coefficient ranges from −0.13 to −0.15%, which agrees well with the literature data for ST ceramics (Viana et al, 1994;Muhamad et al, 2017).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, we also investigated the temperature dependence of the relative permittivity in the temperature range from 20 to 80 • C at 1 MHz. The results showed that a typical value of the temperature coefficient ranges from −0.13 to −0.15%, which agrees well with the literature data for ST ceramics (Viana et al, 1994;Muhamad et al, 2017).…”
Section: Resultssupporting
confidence: 90%
“…Strontium titanate (SrTiO 3 , ST) as a dielectric perovskite material continues to be the focus of intense research due to its high relative permittivity, environmental compatibility, and diverse applicability (Shende et al, 2001). ST-based ceramics are conventionally fabricated by high-temperature solid-state sintering at temperatures around 1,400-1,550 • C and exhibit a relative permittivity of 240 and a dielectric loss tangent of 0.0008 (Muhamad et al, 2017) at 10 kHz. In addition, lithium molybdate (Li 2 MoO 4 , LMO) has been extensively investigated as a dielectric ceramic (Kähäri et al, 2016;Väätäjä et al, 2018), especially with respect to potential applications as patch antennas and humidity sensors (Kähäri et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of this, the ferroelectric domain walls contribute less at high temperature leading to rise in loss tangent factor. Similar dielectric behavior has been reported in the literature for similar category compounds [14,15,17,18]. The variation trends for the doped samples were approximately identical to that for undoped STO0.…”
Section: Dilelectric Characterizationsupporting
confidence: 87%
“…The space charge polarization arising from the movement of ions and defects in the material may be responsible for this increase [13]. There is no curie peak detected in the whole measurement temperature range [14][15]. The high values of dielectric constant at room temperature for STO0 sample may be attributed to the presence of all kinds of polarizations at room temperature which can lead to irregular increase in the permittivities [16][17].…”
Section: Dilelectric Characterizationmentioning
confidence: 99%
“…The increase in dielectric constant for flax‐PP‐Strontium titanate composite at 1 kHz is due to the increase in number of interfaces (flax, polypropylene and strontium titanate instances) for charge accumulation to occur. According to Idris et al 26 the crystal structure of strontium titanate affects the dielectric constant of the composite as it was found that at room temperature strontium titanate exhibits cubic structure, which allows ionic polarization to occur at many instances during the application of an external electric field. Also, Stocker et al's 27 .…”
Section: Resultsmentioning
confidence: 99%